Communication Strategies by English Lecturers and Class Coordinators: An Analysis of Hofstede's Cultural Dimensions - Kadek Mahardika; Ni Luh Putu Sri Adnyani; Dewa Putu Ramendra (STKIP AGAMA HINDU SINGARAJA, 2025)
This study aims to classify the communication strategies used by English lecturers and class coordinators in WhatsApp messages and describe how class coordinators respond to English lecturers' communication strategies in the context of Hofstede's cultural dimensions. This research method uses qualitative descriptive. The instrument in this study is document analysis in the form of screenshots of English Lecturer and Class Coordinator. Data analysis in this study used six steps: (1) Data organization and preparation, (2) Preliminary reading of Data, (3) Data Coding, (4) Developing themes and categories, (5) Detailed analysis and representation, (6) Interpretation of findings. The results of the analysis based on Hofstede's cultural dimensions show that English lecturers generally respond to messages in a relaxed and concise manner, while class coordinators use a more polite and formal tone in their communication. These findings reveal clear differences in communication styles, reflecting the hierarchical dynamics inherent in the educational environment. This study contributes to the understanding of communication practices in academic settings, emphasizing the influence of cultural dimensions on interaction strategies.